Organización Contable a la “Ferretería Granda Quevedo” del cantón Paltas. Periodo octubre – diciembre 2022. - Correa Saritama, Katherine Fernanda (2023)
The Curricular Integration Work called Accounting Organization of "Granda Quevedo Hardware Store" in the canton of Paltas. Period October - December 2022, was developed with the purpose of informing the owner of the economic-financial situation of the company, allowing to know if it is generating profits or losses, if there are debts to be attended or accounts receivable, which guide the owner to make the best decisions that are aimed at its proper functioning. In order to meet the objectives set out, the plan and manual of accounts were prepared with their respective coding and description based on the needs of the business to record each of the daily transactions. Subsequently, a physical verification of the available merchandise, goods and obligations was made, resulting in the following: assets $ 579,364.55, liabilities $ 36,588.48 and equity $ 542. 542,776.07 values that appear in the Inventory and Initial Situation Statement, then the source documentation was ordered chronologically to prepare the Transaction Memorandum and record them in the Daily Book, then each of the accounts was transferred to the General Ledger to make the Trial Balance with the balances and thus make the Worksheet where the adjustments were also reflected and prepare the Statement of Income, Statement of Financial Position, Statement of Cash Flow and Explanatory Notes. Financial indicators of liquidity, activity, indebtedness and profitability were applied to analyze its economic situation based on the results obtained in the Financial Statements. Finally, the conclusions are presented, among which it can be highlighted that Granda Quevedo Hardware Store during the last quarter of the year 2022 presents a profit for the year of $ 2,803.78, results that serve the owner as an input and guide to take corrective measures and implement strategies focused on the improvement of the hardware store.